Satisfacción al cliente en el Minimarket “Voluntad De Dios” de La Ciudadela La Ventura En La Ciudad De Babahoyo. - Madrid Alvario, Magdalena Estefanía (2022)
Customer satisfaction is an important indicator that reveals the effectiveness of business processes; In addition, it is stated that the client who has a high degree of satisfaction can resort to making a new purchase in the commercial establishment. Therefore, it is vital that companies implement sales strategies and tactics that foster strong and lasting business relationships. Therefore, the objective of this case study is to evaluate the customer satisfaction of the "Will of God" Minimarket in order to know what are the factors that condition the perception of the consumer market. The methodology used is constituted by a quantitative and qualitative approach, by virtue of which. The types of research were: descriptive, because the situations found in the study were described in relation to the client's perception, and documentary research, which allowed the collection of information on the variable under analysis. The techniques used are a customer survey and an interview with the business owner, for which questionnaires with well-structured questions were used. The results of the investigation reveal that the human talent of the commercial establishment lacks empathy and cordiality for the development of the commercial process, in the same way problems related to inventory control were identified, which causes not having the stock of products necessary to meet the consumer market needs.